HEALING FACES, RESTORING HOPE: UNLEASHING AI-DRIVEN CLEFT CARE – A NEW ERA IN CRANIOFACIAL SURGERY - DR. RICHA WADHAWAN; DR. ANUJ SHANKAR TIWARI; DR. TARUN JESWANI; DR. CHANCHALA KUMARI; DR. SAI SHUBHAM; DR. SHWETA SHRIVASTAVA (The Bioscan, 2024)
Cleft lip and palate are among the most common congenital deformities, affecting millions of children worldwide. These conditions present significant medical, psychological, and social challenges, necessitating complex multidisciplinary treatment involving surgeries, speech therapy, and continuous care. A comprehensive approach to treatment involves a team of specialists, including oral surgeons, orthodontists, and pedodontists, working collaboratively to provide optimal care. Oral surgeons perform the necessary surgical interventions, orthodontists plan the alignment of teeth and jaws, and pedodontists focus on managing the dental needs of young patients. Together, these professionals ensure that the child’s growth and development are closely monitored and addressed. In many regions, especially low- and middle-income countries, access to care is limited, leading to further disparities in outcomes. However, the emergence of Artificial Intelligence (AI) is transforming cleft care by enhancing diagnostic accuracy, treatment planning, and surgical precision. AI-driven technologies are enabling more personalized interventions, predicting complications, and improving rehabilitation efforts, thereby enhancing both the clinical and emotional outcomes for patients. This review explores the potential of AI in revolutionizing cleft lip and palate management, focusing on its impact on surgical planning, long-term care, and psychosocial support. By integrating AI into cleft care pathways, healthcare providers can optimize treatment strategies, reduce the burden on families, and ultimately offer hope for a brighter future for children born with orofacial clefts.